Language test as boundary object: Perspectives from test users in the healthcare domain. (April 2016) - Macqueen, Susy; Pill, John; Knoch, Ute
Objects that sit between intersecting social worlds, such as Language for Specific Purposes (LSP) tests, are boundary objects – dynamic, historically derived mechanisms which maintain coherence between worlds (Star & Griesemer, 1989). They emerge initially from sociopolitical mandates, such as the need to ensure a safe and efficient workforce or to control immigration, and they develop into standards (i.e. stabilized classifying mechanisms). In this article, we explore the concept of LSP test as boundary object through a qualitative case study of the Occupational English Test (OET), a test which assesses the English proficiency of healthcare professionals who wish to practise in English-speaking healthcare contexts. Stakeholders with different types of vested interest in the test were interviewed (practising doctors and nurses who have taken the test, management staff, professional board representatives) to capture multiple perspectives of both the test-taking experience and the relevance of the test to the workplace. The themes arising from the accumulated stakeholder perceptions depict a 'boundary object' that encompasses a work-readiness level of language proficiency on the one hand and aspects of communication skills for patient-centred care on the other. We argue that the boundary object metaphor is useful in that it represents a negotiation over the adequacy and effects of a test standard for all vested social worlds. Moreover, the test should benefit the worlds it interconnects, not just in terms of the impact on the learning opportunities it offers candidates, but also the impact such learning carries into key social sites, such as healthcare workplaces.